مفهوم الإيمان عند الوعيدية (الخوارج) وموقف أهل السنة والجماعة- دراسة تحليلية مقارنة - المشيطي سليمة جمعة علي (Al-Qurtas, 2025)
مفهوم الإيمان عند الوعيدية (الخوارج) وموقف أهل السنة والجماعة- دراسة تحليلية مقارنة